2021
DOI: 10.3389/fpubh.2021.702965
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Social Isolation Among Community-Dwelling Older Adults During the COVID-19 Pandemic

Abstract: Background: The past year has severely curtailed social interactions among older adults given their high rates of COVID-19 morbidity and mortality. This study examined social, behavioral, and medical correlates of social isolation among community-dwelling older adults during the COVID-19 pandemic and stratified findings to explore unique differences in two typically neglected populations, African American and Hispanic older adults.Methods: Working with community-based organizations and senior living centers, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…This may have led to social isolation. Similarly, it is well known that the great majority of those who reported social isolation had one or more chronic conditions [ 45 ]. Moreover, during the pandemic, there were reports of older people abandoned in care homes, making them more vulnerable to social isolation and loneliness, with an increased risk of anxiety, depression, cognitive dysfunction, heart disease and mortality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may have led to social isolation. Similarly, it is well known that the great majority of those who reported social isolation had one or more chronic conditions [ 45 ]. Moreover, during the pandemic, there were reports of older people abandoned in care homes, making them more vulnerable to social isolation and loneliness, with an increased risk of anxiety, depression, cognitive dysfunction, heart disease and mortality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported similar findings [ 35 , 37 40 ]. This is not surprising, given that comorbidities represent a risk factor for more severe covid-19 presentations [ 41 ] and might be associated with higher levels of distress in both children and parents of those children [ 42 ], and more strict social distancing [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency housing information was made available for those at risk of homelessness. An urgent need arose to focus efforts on addressing loneliness and social isolation for patients and caregivers alike, and the disparities linked to loneliness in these populations were significant (Adepoju et al, 2021(Adepoju et al, , 2022Kotwal et al, 2021). GWEP-FQHC partnerships created programs to address social isolation.…”
Section: Challenge 3: New Social Determinants Of Health Gapsmentioning
confidence: 99%